Lipid organization in xerosis: the key of the problem?. (13th November 2018) - Vyumvuhore, R.; Michael‐Jubeli, R.; Verzeaux, L.; Boudier, D.; Le Guillou, M.; Bordes, S.; Libong, D.; Tfayli, A.; Manfait, M.; Closs, B.
Abstract: Objective: Although xerosis is a common skin disorder among the population, there is no in vivo global study focusing on xerotic skin. Hence, the objective of this study was to characterize xerotic skin from the surface to the molecular scale with in vivo and non‐invasive approaches. Methods: For this purpose, 15 healthy volunteers with normal skin and 19 healthy volunteers with xerotic skin were selected by a dermatologist, thanks to a visual scorage. Firstly, the skin surface was characterized with biometric measurements. Then, the state of skin dryness was assessed by in vivo confocal microscopy. The molecular signature of xerotic skin was then determined by in vivo confocal Raman microspectroscopy. Finally, an identification of stratum corneum (SC) lipids was performed using Normal phase liquid chromatography (NP‐LC) coupled to two detectors: Corona and High Resolution/Mass Spectroscopy (HR/MS). Results: Results obtained at the skin surface displayed an increase in the transepidermal water loss (TEWL) and a decrease in the hydration rate in xerotic skin. Confocal microscopy revealed an alteration of the cell shape in xerotic skin. Moreover, confocal Raman microspectroscopy demonstrated directly in vivo and non‐invasively the lack of organization and conformation of lipids in this skin. Finally, HPLC analyses revealed that the three ceramide sub‐classes (NdS, NS and EOP) significantly decrease in xerosis. Altogether, these results identify parameters for the characterization of xerotic skin compared to normal. Conclusion: This study highlighted discriminative parameters from the surface to the molecular level in vivo and non‐invasively between xerotic and normal skins. These results will be useful for the development of new cosmetic active ingredients dedicated to xerotic skin.